FACTORS INFLUENCING THE DECISION TO PURCHASE PRODUCTS PRODUCED BY COMMUNITIES OF CONSUMERS IN THAILAND - Wasanakamon, Wisanu; Asawawongwichit, Thanabordee (Journal of MCU Nakhondhat, 2024)
The purpose of this research is to study the factors that influence consumer decisions to purchase community - produced products in Thailand, by analyzing the marketing mix factors that affect the selection of community-produced products and testing the relationship between personal factors and the selection of community - produced products in Thailand. This study is quantitative research. The data was surveyed using questionnaires from 400 samples of consumers of products produced by communities living in Thailand. The data was analyzed using statistics, frequency, percentage, mean, standard deviation, and hypothesis testing using Chi - square test. The research results found that the consumers who purchase community-produced products are mostly adults 40 - 54 years old. They buy food products the most, there is a cost per purchase of approximately about 301 - 500 baht, places to buy products are souvenir shops, and receive news information from online channels. The reason for choosing to buy products from the community is to help promote and support Thai products. The overall marketing mix factor affects product selection produced by the community at a high level with an average of 4.17. The findings indicate that the marketing mix factors significantly influence product selection with an average of 4.22, with consumers prioritizing price. Furthermore, the analysis of personal factors revealed that gender, age, education level, monthly income, number of family members, and residential areas are statistically significant in influencing consumer behavior towards community - produced products. However, marital status and occupation did not show statistical significance.